2009
DOI: 10.2166/wst.2009.316
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature on the hydrolysis, acidogenesis and methanogenesis in mesophilic anaerobic digestion: parameter identification and modeling application

Abstract: The effect of temperature on the kinetic parameters involved in the main reactions of the anaerobic digestion process was studied. Batch tests with starch, glucose and acetic acid as substrates for hydrolysis, acidogenesis and methanogenesis, respectively, were performed in a temperature range between 15 and 45 degrees C. First order kinetics was assumed to determine the hydrolysis rate constant, while Monod and Haldane kinetics were considered for acidogenesis and methanogenesis, respectively. The results obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
2
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 17 publications
6
50
2
9
Order By: Relevance
“…In contrast to the work of Donoso-Bravo et al (2009), which showed that a temperature increase from 37 °C to 40 °C negatively affected acidogenesis and subsequent methanogenesis, our results indicate that a smooth transition from mesophilic operation at 37 °C to thermophilic operation at 55 °C enables a stable biogas production.…”
Section: Mesophilic Vs Thermophilic Operation In Anaerobic Digesterscontrasting
confidence: 99%
“…In contrast to the work of Donoso-Bravo et al (2009), which showed that a temperature increase from 37 °C to 40 °C negatively affected acidogenesis and subsequent methanogenesis, our results indicate that a smooth transition from mesophilic operation at 37 °C to thermophilic operation at 55 °C enables a stable biogas production.…”
Section: Mesophilic Vs Thermophilic Operation In Anaerobic Digesterscontrasting
confidence: 99%
“…Hydrolysis constant is of major interest in the context of biogas production as hydrolysis is known to be the speedlimiting step in digesting conventional biomass (Donoso-Bravo et al, 2009). Anaerobic wastewater digestion is rather dominated by methanogenesis as the speed-limiting step as there is nearly no particulate matter that needs to be hydrolyzed prior to methanation (Donoso-Bravo et al, 2009;Wirth and Mumme, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrolysis and methanogenesis are considered to be rate limiting steps in the methane fermentation process (7), and obligatory or facultatively syntrophic associations between various bacteria and archaea are reported to be involved in the methanogenesis from some compounds (8). This complexity makes it difficult to investigate the factors influencing the microbial consortia in methanogenic environments under bioelectrochemical control.…”
mentioning
confidence: 99%